Role of media coverage in mitigating COVID-19 transmission: evidence from China - Liu, Ning; Chen, Zhuo; Bao, Guoxian (Elsevier Inc., 2020)
This paper evaluates the impact of media coverage in mitigating the spread of COVID-19 in China during the early phase of the pandemic. We construct provincial-level data on media coverage and link with COVID-19 indicators and population mobility data, among other control variables. We estimate how media coverage mitigates the temporal and spatial spread of COVID-19. Seemingly unrelated regressions are used to examine the simultaneous impact of media coverage on the number of new cases and close contacts. The results show that the effect of media coverage on COVID-19 transmission in China has an inverse-U curvature and was mediated by within- and across-province population mobility. Based on our simulation results, media coverage in China is associated with a potential reduction of 394,000 COVID-19 cases and 1.4 million close contacts during January 19 and February 29. Our results also support the important role of contact tracing in mitigating the transmission of COVID-19.